Injuries and trauma in the minds of long distance runners - Zuzanna Piekorz; Andrzej Lewandowski; Krzysztof Szarski; Agnieszka Radzimińska; Katarzyna Strojek; Hanna Styczyńska; Walery Zukow (Kazimierz Wielki University, 2017)
Introduction: Running is a fundamental and universal form of movement is manifested by man. Now it is increasingly carried out in the framework of the recreation movement or health training, becoming an increasingly popular form of physical activity. Despite the many benefits of walking tracks, an increasing number of injuries and injuries among persons taking up this kind of physical activity. Objective: It is the assessment of consciousness runners in terms of knowledge about the injuries and injuries most often occur among persons taking up training, as well as review the applicable training and knowledge of the issues related to his theory.  Material and methods: Using the author's questionnaire survey examined 93 people taking part in the II Half Marathon results test was developed, not part of the chi square test, and test the equality of two aspect ratio structures rates based on statistics Z. Results: It was found that among the participants of the bulk transmission are the largest group of men with higher education, living in large cities. It has been shown statistically significant difference in the incidence of injuries among both men and women (K:22, 2% M:43,9%, chi-square = 3.8503 p = 0,0497), at the same time revealing similar technical preparation groups studied. As a caller injuries respondents pointed to the excessive burden on joints, and this result was confirmed injuries of the knee as the most common among the subjects. Conclusions: Found a high proportion of injuries among the test group of runners, points to the inadequate preparation of physical, technical and methodical and likely application of the excessive burdens training especially by men.